Influence of University Students' Demographics and Their Learning Styles: A Study of UUM's Students in Bank Rakyat Residential College - Ma, Lei (2010)
This paper investigates the relationship between students' demographics factors and the learning style preferences of students. By linking Kolb' model of learning style preferences to the students demographics differences of individual learners the researcher develop a study by data collected from 100 students from different nation backgrounds enrolled in different courses at university in Utara Malaysia. The finding show that learning style preferences differ across nationalities, gender, race, educational background and that these preferences are affected by a number of cultural values. We also find important differences in the learning styles of male and female students and between local and exchange students. The results are of importance to teachers and managers active in the education and development of individuals from different academic background and for researcher's influences in the influences of academic improvements on learning style preferences.